2014
DOI: 10.1016/j.ajog.2013.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between 17-alpha hydroxyprogesterone caproate concentration and spontaneous preterm birth

Abstract: Objective 17-alpha hydroxyprogesterone caproate (17-OHPC) 250 mg weekly reduces recurrent spontaneous preterm birth (SPTB) in women with a prior SPTB by 33%. The dose is not based on pharmacological considerations. A therapeutic concentration has not been determined hampering any attempt to optimize treatment. This study evaluated the relationship between 17-OHPC plasma concentrations and the rate of SPTB in women with singleton gestation. Study Design A single blood sample was obtained between 25 and 28 wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 18 publications
(21 reference statements)
2
35
0
Order By: Relevance
“…3,[18][19][20][21] Some studies have shown that protease inhibitors reduce progesterone production in the trophoblast in vitro and that low progesterone levels are associated with preterm delivery. [22][23][24][25] However, other studies have shown that nevirapine-based ART is also associated with a higher rate of preterm delivery than zidovudine plus single-dose nevirapine. 5,6 The PROMISE trial was not designed to compare protease inhibitor-based ART with NNRTI-based ART, and we cannot comment on whether the current WHO-recommended ART regimen of tenofovir, emtricitabine, and efavirenz would be associated with a lower risk of low birth weight or preterm delivery than the ART regimens in the PROMISE trial.…”
Section: Discussionmentioning
confidence: 88%
“…3,[18][19][20][21] Some studies have shown that protease inhibitors reduce progesterone production in the trophoblast in vitro and that low progesterone levels are associated with preterm delivery. [22][23][24][25] However, other studies have shown that nevirapine-based ART is also associated with a higher rate of preterm delivery than zidovudine plus single-dose nevirapine. 5,6 The PROMISE trial was not designed to compare protease inhibitor-based ART with NNRTI-based ART, and we cannot comment on whether the current WHO-recommended ART regimen of tenofovir, emtricitabine, and efavirenz would be associated with a lower risk of low birth weight or preterm delivery than the ART regimens in the PROMISE trial.…”
Section: Discussionmentioning
confidence: 88%
“…55 Studies with primary human chorion cells, and in a mouse inflammatory-mediated parturition model, suggest that MPA may be more promising than HP for prevention of preterm birth. [56][57][58][59] However, the only randomized clinical trial to use MPA to prevent prematurity in at-risk pregnancies failed to demonstrate benefit.…”
Section: Commentmentioning
confidence: 98%
“…In 315 women with a singleton gestation receiving 17-OHPC weekly, the concentrations ranged between 3.7–56ng/mL between 25 and 28 weeks of gestation 53 . Women with 17-OHPC plasma concentrations in the lowest quintile had a higher risk of recurrent spontaneous preterm birth compared to women in the third to fifth quintiles (36.5% vs. 25%, Figure 3).…”
Section: Pharmacodynamic Properties Of 17-ohpcmentioning
confidence: 99%